Analysis of Medical Responsibility for the Risks of Clinical Trials of the TB Vaccine in Indonesia: A Case Study on Legal Protection for Research Subjects - Tony Richard Alexander Samosir (Interdisciplinary Social Studies, 2026)
Indonesia is a country governed by the rule of law, which provides legal guarantees and protection for all its citizens, including in matters related to health services. This protection also extends to individuals who participated as subjects in the TB vaccine clinical trials conducted several months ago. These circumstances raise questions regarding the forms of medical and legal responsibility owing to clinical trial subjects when risks arise during or after the research. They also prompt an examination of whether the informed consent procedures and legal safeguards applied in the TB vaccine clinical trials in Indonesia align with the principles of fairness and safety for research participants. This brief study employs a normative juridical approach, relying on secondary data obtained through library research. The findings indicate the following: First, medical and legal responsibilities toward TB vaccine clinical trial subjects in the event of risks occurring during or after the research include the obligation to report such incidents to the Ethics Committee and to accept the consequences of any errors committed. Second, the informed consent mechanisms and legal protections implemented in TB vaccine clinical trials in Indonesia do not fully satisfy the principles of fairness and safety for research subjects.